2021
DOI: 10.1080/03096564.2021.1943620
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Historical Multilingualism and Language Contact ‘from Below’. Evidence from the Dutch-German Borderlands in the Long Nineteenth Century

Abstract: European language histories, including the history of Dutch, have often been portrayed as broadly linear developments towards one uniform standard language. In this biased account, rooted in the nation-building era around 1800, language diversity and multilingualism were largely rendered invisible. Against the background of clearly segregated spaces, politically and linguistically, border settings have particularly challenged the monolingual ideology of 'one nation-one language'. Taking a historical-sociolingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…On the historical side, two studies demonstrated how narratives about the imposition of a dominant language can erase the multilingual reality and threaten minorities' linguistic rights. Andreas Krogull's research on historical multilingualism and language contact in the Dutch-German borderlands in the long nineteenth century challenges the traditional narrative of "one language-one nation", underpinned by an ideology of clearly separated linguistic and political spaces which has rendered the multilingualism of speakers and writers invisible (Krogull 2021). Through painstaking archival research and a close reading of family archives and collections of letters, Krogull shows how, despite the growing importance of nation-states and their standard languages, multilingual practices and contact phenomena can be traced in the private sphere and that the Dutch-German borderlands remained a multifaceted sociolinguistic space well into the nineteenth century.…”
Section: Case Study 2: Linguistic Rights Language Status and Powermentioning
confidence: 99%
“…On the historical side, two studies demonstrated how narratives about the imposition of a dominant language can erase the multilingual reality and threaten minorities' linguistic rights. Andreas Krogull's research on historical multilingualism and language contact in the Dutch-German borderlands in the long nineteenth century challenges the traditional narrative of "one language-one nation", underpinned by an ideology of clearly separated linguistic and political spaces which has rendered the multilingualism of speakers and writers invisible (Krogull 2021). Through painstaking archival research and a close reading of family archives and collections of letters, Krogull shows how, despite the growing importance of nation-states and their standard languages, multilingual practices and contact phenomena can be traced in the private sphere and that the Dutch-German borderlands remained a multifaceted sociolinguistic space well into the nineteenth century.…”
Section: Case Study 2: Linguistic Rights Language Status and Powermentioning
confidence: 99%